Pengaruh Project Based Learning dalam Meningkatkan Keterampilan Kolaborasi Siswa - Nur Balkis; Zulfikar; Mauliana Wayudi (INDO PUBLISHING, 2025)
This study aims to determine the effect of the Project Based Learning model on improving students’ collaboration skills in Social Studies learning in Grade VIII at UPTD SMPN 1 Peusangan. This study uses a quantitative approach with a quasi-experimental design. The research sample consisted of 64 eighth- grade students, evenly divided into two groups: 32 students in the experimental class who received treatment using the Project Based Learning model, and 32 students in the control class who received conventional learning. The data collection instrument used was a student collaboration skills questionnaire. Data analysis included normality test, homogeneity test, and hypothesis testing using SPSS Statistics 25 software. The results of hypothesis testing using the Paired Sample t-test showed a significance value of 0.000 (p < 0.05), so H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that there is a significant effect of the implementation of the Project Based Learning model on improving students’ collaboration skills in Social Studies learning in Grade VIII at UPTD SMPN 1 Peusangan.